Time to put a spotlight on out-patient chronotherapy for depression. Issue 6 (24th November 2021) - Kallestad, Havard; Scott, Jan
Summary: The challenge of identifying efficacious out-patient treatments for depression is amplified by the increasing desire to find interventions that reduce the time to sustained improvement. One potential but underexplored option is triple chronotherapy (TCT). To date, use of TCT has been largely restricted to specialist units or in-patients. Recent research demonstrates that it may be possible to undertake sleep deprivation in out-patient settings, raising the possibility of delivering TCT to broader populations of individuals with depression. Emerging evidence suggests that out-patient TCT is a high-benefit, low-risk intervention but questions remain about how to target TCT and its mechanisms of action. Like traditional antidepressants, TCT probably acts through several pathways, especially the synchronisation of the 'master clock'. Availability of reliable and valid methods of out-patient measurement of intra-individual circadian rhythmicity and light exposure are rate-limiting steps in the wider dissemination of TCT.